A comparative X-ray diffraction analysis of Sr2+substituted hydroxyapatite from sand lobster shell waste using various methods - Arian Hermawan Diputra; I Kadek Hariscandra Dinatha; Yusril Yusuf (Heliyon)
This study aims to investigate the crystallographic properties of hydroxyapatite (HAp) and strontium-substituted hydroxyapatite (SrHAp) obtained from sand lobster shells (SLS) using various analytical methods. HAp and SrHAp were synthesized by the hydrothermal method using sand lobster (Panulirus homarus) shell waste as a calcium precursor. SLS were calcined at 0 °C, 600 °C, 800 °C, and 1000 °C and characterized by X-ray diffraction (XRD). HAp and SrHAp were analyzed by XRD and transmission electron microscopy (TEM). XRD results revealed that SLS calcined at 1000 °C displayed a Ca(OH)2 phase, while those calcined at other temperatures showed a CaCO3 phase. The characterization also verified the diffraction patterns of HAp and SrHAp according to the reference model. Various methods, including the Scherrer method, linear straight-line Scherrer method, Monshi-Scherrer method, Williamson-Hall plot, size-strain plot, and Halder-Wagner method, were employed to investigate the microstructure parameters (crystallite size and microstrain). All methods resulted in varied yet comparable results of crystallite size, except for the linear straight-line Scherrer method. The TEM results showed that the particle sizes of HAp and SrHAp were approximately 130 nm. In this study, the W-H plot was regarded as the best method for providing additional information on anisotropy elasticity and consistent crystallite size results.